Are the Central and Eastern European Transition Countries still vullnerable to an Financial Crisis? Results from the Signals Approach - Axel Brüggemann; Thomas Linne (Leibniz-Institut für Wirtschaftsforschung Halle (IWH), 2002)
The aim of the paper is to analyse the vulnerability of the Central and Eastern European accession countries to the EU as well as that of Turkey and Russia to a financial crisis. Our methodology is an extension of the signals approach. We develop a composite indicator to measure the evolution of the risk potential in each country. Our findings show that crises in Central and Eastern Europe are caused by much the usual suspects as in others emerging markets. In particular an overvalued exchange rate, weak exports and dwindling currency reserves have good predictive power for assessing crisis vulnerabilities.
urn:nbn:de:gbv:3:2-20093
Keywords: F31; F47; 330; financial crises; vulnerability indicator; central and eastern Europe; Währungskrise; Wirtschaftsindikator; Kaufkraftparität; Export; Währungsreserven; Schätzung; Osteuropa; Türkei; Russland; Finanzkrise